Local shelter plan 2022-2023 municipality of Hamtik - Andreo, Angelic Jessie Ruth M. (University of the Philippines Visayas, 2022)
The plan has a timeframe of 9 years, covering period 2021 to 2030. This is broken down into three Planning periods. The target population that the LSP addresses totals to 1,490 households. This is constituted of households classified as the backlog, the future need resulting frm increase in population, and those with upgrading needs. majority of them have marginal and informal sources of income. Shelter needs are classifies into NEW NEEDED and UPGRADING NEEDS. New units needed refers to the number of units required to respond to the backlog and the future need. The backlog is computed to be 641 units. It is composed of the displaced totaling six hundred-five (605) households, likewise the doubled-up or sharers totaling to thirty-six (36) households, and zero (0) homeless. These data reveal that 94.39 % of the housing stock comprises the displaced units, 5.62% are dobled-up,while 0 are homeless. The displaced units/households are made up of households presently occupying danger areas, sites to be used for government infrastructure projects, households issued with court orders for eviction or those are potential for displacement due to climate change and other hazards. With an average annual growth rate of 1.37%, an additional 2,131 new households are expected to make up the future need within the period covered by the plan. There are 163 households needing tenurial upgrading. They comprise 1.43% of the housing stock. There are, likewise, households needing upgrading of various basic services; to wit: 365 households (4.69% of housing stock) need upgrading of power facility, 2794 households (24.51%) needs upgrading of water facility; 1,238 households (10.38%) needs upgrading of sanitary facility; 70 households (0.61%) needs upgrading of roads; 70 households 0.61%) needs upgrading of drainage; 3,501 households (30.71%) needs upgrading of garbage collection and disposal. There is also an estmated 7.29% or 831 units that need structural improvement or upgrading to make these houses safe for habitation. Affordability of Households for New Housing and affordable Housing Options. The target population to be provided with housing assistance are classified into six income groups, and an affordable housing option is recommended for each groups. The 1st income group is composed mainly of households of Drivers, Laborers, Small scale fishermen, Vendors, Household services, etc. with monthly household income falling below the poverty threshold estimated to be 9,200.00 and below. With a typical household monthly income of 8,400.00, their affordable housing option is 24-sq. m. row house without loft and land development and facilities will be provided by the municipal government through NHA programs payable in 30 years at 3% interest. It is estimated that 31.7% of the total new units needed will be for the first income group. Majority of those belonging to the 2nd income group are families of Farming, skilled workers, Pensioner's, Employment in Government agencies & Private Firms, etc. with typical monthly household income of P12,100.00. Their affordable housingoption, 33 sq. m. row house with loft, land development and facilities will be provided by the municipal government through NHA progrms paayable in 30 years at 3% interest. Based on the estimates, 23% of the new units are needed by households belonging to this group. The 3rd income group has a typical household monthly income of P22,500.00 and is composed of 40.25 sq. m. lot size. Developed Land which includes concrete roads, covered drainage, septic vaults, electrical connection; with 28 sq. m. Row house without loft. Their affordable housing option is payable in 30 years at 6% interest. Approximately 28.3% of the new units needed is for the third income group. The 4th income group comprises the families or households whose bread winners are heads of offices/Supervisor/OFW-supported families receiving P30,001.00-P45,000.00 monthly with typical monthly household income of 37,500.00. Their affordable housing option is 58.33 sq. m. lot size. Developed land which includes concrete roads, underground drainage, septic vaults, electrical connection; with 28 sq. m. duplex, payable in 25 years at 85 interest. Of the total new units needed, 9.4% is needed by this income group. The 5th income group includes of fmilies of professionals/managers earning P45,001.00-P60,000.00 monthly with a typicaal monthly household ncome of P52,500.00. Their affordable housing option is 60 sq. m. developed land which includes concrete roads, underground drainage, septic vaults,electrical connection; with 32 sq.m. Single-detached 2 storey complete house payable in 25 years at 105 interest. Of the total new units needed,3.70% is needed by this income group. To accommodate and address the shelter needs of all the targeted households, an aggregate of 12.58 hectares is needed and the financial requirements to put up the recommended housing units totals to about P1,257,497,188.00.